2022
DOI: 10.1177/10556656221104937
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Bone Grafting Practice Patterns in North American Cleft Surgeons

Abstract: Introduction Alveolar bone grafting aims to restore bony continuity of the alveolus and provide optimal periodontal support for teeth adjacent to the cleft. We created a survey of cleft surgeons to assess the current standard of care regarding this procedure. Methods A multiple choice survey was implemented using Qualtrics software and emailed to a list of 708 surgeons from the ACPA membership directory. Correlation between various provider factors and treatment practices was assessed with Fisher's exact test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…This was supported by researchers who reported that secondary bone grafting after expansion of the maxilla was the most popular practice among oral surgeons and others who reported that the iliac crest was considered to be the best donor site for an alveolar bone graft. It helped in the stabilization of the cleft maxilla after expansion and aided in maintaining the continuity of the arch [ 8 , 9 ]. Clinicians radiographically proved similar advantages of secondary bone grafting with expertise in cleft care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by researchers who reported that secondary bone grafting after expansion of the maxilla was the most popular practice among oral surgeons and others who reported that the iliac crest was considered to be the best donor site for an alveolar bone graft. It helped in the stabilization of the cleft maxilla after expansion and aided in maintaining the continuity of the arch [ 8 , 9 ]. Clinicians radiographically proved similar advantages of secondary bone grafting with expertise in cleft care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]15,16 Among North American cleft surgeons, 23% report using allograft bone products, and 31% employed rhBMP-2. 6 This study presents a novel approach for alveolar reconstruction by combining CBM with rhBMP-2 for revision ABG in UCLP and BCLP following failed autologous ABG. Outcomes were evaluated using operative and orthodontic FACE 5 (1) data and volumetric analysis with cone beam computed tomography (CBCT).…”
Section: Introductionmentioning
confidence: 99%
“…5 Parents often desire an alternative to ABG with an autologous iliac crest graft, and cleft surgeons are utilizing an increased number of non-autologous materials. 6 Allografts, which utilize bone graft substitutes, offer an alternative to alveolar ridge reconstruction. These allograft materials are readily available, user-friendly, reduce operative times, and eliminate donor site pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When ABG is carried out after the cleft lip and palate have been repaired, it is defined as secondary ABG. The timing generally assumed as the optimal timing for ABG is between the ages of 9 and 11 years, when the root of the permanent canine at the cleft side has reached between 50 and 75% of its final length [3][4][5][6][7]. This approach, called late secondary ABG, has proven to be more successful for subsequent maxillary growth compared to the previously used primary bone grafting [8].…”
Section: Introductionmentioning
confidence: 99%